Woman is Not Independent of Man. And Man is Not Independent of Woman: The Order of the Creation of Man and Woman in 1 Corinthians 11:2–16 - LI, Hao (Journal of Research for Christianity in China (JRCC), 2023)
Paul's epistle reference to the order of the creation in Genesis is often seen as a commonly accepted principle for establishing normative principles in relationships between genders. This paper analyzes the purpose and nature of the references to the order of creation in 1 Corinthians 11:2-16. By employing a methodology that combines intertextuality and socio-cultural contextualization, this paper evaluates and interprets the passage within their writing contexts, sociological contexts, and the interpretive history of Second Temple Judaism. The study indicates that in response to the honor-shame culture prevalent among the Corinthian audience, 1 Corinthians 11:2-16 dialectically emphasizes both the "subordination of women to men" and the "mutual reciprocity and unity" of genders, encompassing both cultural adaptation and countercultural intentions. Considering the contextual flow and theological development of 1 Corinthians, the study demonstrates that Paul's main aim is to establish a relationship of mutual reciprocity and unity between genders, rather than establishing an absolute principle of female subordination to male based on the order of creation beyond time and space.
Keywords: The order of the creation, 1 Corinthians 11:2-16, Contextualization, Intertextuality, Intertestamental Period